2020
DOI: 10.1186/s40463-020-00473-y
|View full text |Cite
|
Sign up to set email alerts
|

Age based evaluation of nut aspiration risk

Abstract: Objective To identify an age at which initiation of whole nut into the pediatric diet could be considered safe, by evaluating the age distribution of children undergoing bronchoscopy with removal of nut or seed material from the airway. Method A retrospective chart review over a ten-year period identifying children age 0–18 that have undergone bronchoscopy with retrieval of airway foreign bodies. A statistical analysis of demographic data was carried out to identify age distribution of aspiration events. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…The vast majority of our cohort had aspirations less than 3 years of age, which was in line with other reviews 2 . Thus, it was suggested that nuts in diets should better be introduced after the age of 3 years, under close supervision 2 …”
supporting
confidence: 90%
See 3 more Smart Citations
“…The vast majority of our cohort had aspirations less than 3 years of age, which was in line with other reviews 2 . Thus, it was suggested that nuts in diets should better be introduced after the age of 3 years, under close supervision 2 …”
supporting
confidence: 90%
“…Toddlers are particularly susceptible to aspiration during feed, which could be attributed to their weak protective reflexes, as well as immature chewing and swallowing mechanisms 6 . The vast majority of our cohort had aspirations less than 3 years of age, which was in line with other reviews 2 . Thus, it was suggested that nuts in diets should better be introduced after the age of 3 years, under close supervision 2 …”
supporting
confidence: 85%
See 2 more Smart Citations
“…Nuts must be crushed, ground or served as nut or seed butter (such as peanut butter). It is important to avoid giving whole nuts and similar hard foods to young children to reduce the risk of choking [48].…”
Section: Plant-rich Dietmentioning
confidence: 99%